Business Sustainability Strategy: A Business Model Canvas Approach - Jeni Susyanti; Nila Kusumawati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This literature research aims to build hypotheses regarding the influence between variables, which can later be used for further research in business management. The literature review research article Business Sustainability Strategy: A Business Model Canvas Approach is a scientific literature article within the scope of business management science. The approach used in this literature review research is descriptive and qualitative. The data collection technique is to use literature studies or review relevant previous articles. The data used in this descriptive qualitative approach comes from previous research relevant to this research and sourced from academic online media such as Thomson Reuters Journals, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journals, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) The utilization of business model canvas (BMC) analysis has proven to be an effective instrument in the formulation of business sustainability strategies. By using a systematic methodology, the business model canvas (BMC) allows companies to gain insight and identify the core elements of their business model, including value propositions, customer segments, and distribution channels. This is particularly important in the context of sustainability, where companies are obliged to pursue profits while considering the social and environmental consequences of their operations; and 2) The implementation of business sustainability strategies through the business model canvas has an important impact on the financial and non-financial performance of companies. In terms of financial performance, companies that integrate sustainability principles into their business models tend to show improved operational efficiency, reduced costs, and increased customer loyalty.